Study of changes in proteolytic systems of rats under conditions of experimental chronic prostatitis - Kashtelyan, O.; Savytskyi, I.; Liulko, S.; Mizevych, Y.; Sarahan, V. (Journal of Education, Health and Sport, 2022)
The aim of our research – to analyze the mechanisms of regulation of the body’s proteolytic systems during inflammation, detection of inflammation markers in blood and prostate secretions in the simulation of chronic prostatitis (CP) in rats. 1. The leading link in the pathogenesis of many diseases is a change in the structure and functions of biological membranes – membranopathy, the consequence of which is a violation of histochemical barriers, which is manifested in an increase in the excretion of certain metabolites in the extracellular fluid. In the case of experimental CP in rats, the appearance in the secretion of the prostate gland of the components of KKS, which are determined in the secretion of the normal prostate in trace amounts, was noted. Inflammatory damage to the prostate was also evidenced by an increase in the proteolytic potential of prostate secretion due to an increase in kallikrein activity on the 21st day by 807.1% (р˂0.05), which leads to massive kininogenesis. Depletion of the adaptive and compensatory potential of the prostate gland was evidenced by a decrease in prekallikrein by 21.7% (р˂0.05) compared to the intact group of animals. A sharp increase in the activity of kallikrein in CP is probably compensated by an increase in the activity of its specific inhibitor – α2-macroglobulin, the level of which in the secretion of the CP increased on 225 % on the 21st day of the experiment compared to intact rats, and the increase in proteolytic potential – by an increase of 125 % in the inhibitory activity of α1-PI, a protein of the acute phase of inflammation. An increase in the content and activity of KKS components in the secretion of the prostate testifies to its inflammatory damage and violation of the permeability of the hematoprostatic barrier, which can be an important diagnostic criterion.